FACTORS DETERMINING EMPLOYEE PERFORMANCE IN THE CIGAR COMPANIES - Hendrawijaya, Arief Tukiman; Imsiyah, Niswatul; Gumanti, Tatang Ary (Universitas Brawijaya, Indonesia, 2019)
This study aimed to analyze the influence of age, gender, education, length of service and number of dependents on employee performance. This is survey-based research, using cross-sectional study. The samples consist of employees in the cigar companies in Jember Regency. Determination of the research sample using stratified random sampling by selecting ten respondents from each cigar company. From a total of 14 companies, the total samples consist of 140 respondents. The results show that age, gender, education, years of service, and the number of family dependents had a significant positive effect on employee performance. Further research may examine employee performance in companies engaged in other fields.